The Effects of Digital Marketing, Price Perception, and Brand Image on Consumer Purchase Intention on Yuli Kebaya Bali - Ni Kadek Ayu Dwita Metiari; Ni Wayan Eka Mitariani; Ni Putu Nita Anggraini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
This study aims to determine the influence of digital marketing, price perception, and brand image on consumer purchase intent toward Yuli Kebaya Bali. The increasingly fierce business competition in the traditional Balinese clothing sector, as well as fluctuations in consumer purchasing power affecting Yuli Kebaya Bali, make consumer purchase intent a critical factor in business sustainability. Therefore, an appropriate marketing strategy is needed to boost consumer purchase intent. This study employs a quantitative approach using a survey method. The population consists of all Yuli Kebaya Bali consumers. The sampling technique utilized accidental sampling, with a sample size of 105 respondents. Data were collected through the distribution of questionnaires and analyzed using multiple linear regression analysis. The results of the study indicate that digital marketing has a positive and significant effect on consumer purchasing interest in Yuli Kebaya Bali. Price perception has a positive and significant effect on consumer purchasing interest in Yuli Kebaya Bali. Brand image has a positive and significant effect on consumer purchasing interest in Yuli Kebaya Bali. Based on the results of the study, it can be concluded that digital marketing, price perception, and brand image play a crucial role in increasing consumer purchasing interest.